P084 EDS ECHO: virtual case based learning in the assessment and management of Ehlers-Danlos syndrome and hypermobility spectrum disorders. (26th April 2021) - Hakim, Alan; Schubart, Jane; Francomano, Clair; Bascom, Rebecca; Bloom, Lara
Abstract: Background/Aims   The Ehlers-Danlos Society is an affiliate of Project ECHO, a non-profit organisation supporting health professionals manage their patients through telehealth case-based learning. To increase access to expert advice and learning, in 2019 the Ehlers-Danlos Society introduced EDS ECHO, a series of programmes for health professionals supporting them in learning and sharing knowledge in the management of Ehlers-Danlos syndromes (EDS) and hypermobility spectrum disorders (HSD). Programmes run from the UK, USA, and Australia; participants and experts joining from all over the world, and, from multiple specialties. This study explores participant perceptions of a 9-session programme covering all aspects of diagnosis and management in EDS and HSD, and, their co-morbidities. Each session is 90 minutes long, providing a total of 13.5 hours of learning. All materials are made available for review. The programme is repeated throughout the year. Methods   The study had IRB approval from Penn State, USA. At the beginning of each 9-session programme, participants were invited to join the study. Using REDCap, a series of questions surveyed the participants confidence in managing patients with EDS or HSD; and, re-explored this at 6 months following completion of the programme. In addition, participants were surveyed for their perceptions of the value of the programme. Results   185 of 237 eligible participants completed the baseline and 6-month follow-up survey. At baseline 17%, 47%, and 36% reported their levels of confidence in diagnosing EDS or HSD as either low, moderate, or high respectively. The most reported motivations for joining the programme were: to increase knowledge (90% of responders), access experts (71%), and, increase confidence in managing EDS and HSD (68%). At 6-month follow-up 80-95% of participants reported positive experiences across the various fields of enquiry. With regard to increasing level of knowledge 46% reported a 'slight' increase and 46% a 'great' increase. Levels of confidence in diagnosis and management had risen 'slightly' in 54% and 'greatly' in 40% of participants. 78% of participants reported an overall increase in their interest in EDS and HSD. Conclusion   The Project ECHO model of 'all teach all learn', case-based learning, and use of telehealth technology is well-established in supporting healthcare professionals managing patients across the breadth of Medicine. EDS ECHO follows these principles and practices, providing a series of programmes aligned to the multiple disciplines that manage people with EDS and HSD. For the majority of participants their perception was that the EDS ECHO 9-week program increased their knowledge and confidence in assessing and managing EDS and HSD. Further analysis will explore themes for developing the program, and how changes in confidence are influenced by baseline perceptions. In addition, a study is underway to explore perceptions of care among patients of participants in the EDS ECHO programme. Disclosure   A. Hakim: Consultancies; The Ehlers-Danlos Society. J. Schubart: Grants/research support; The Ehlers-Danlos Society. C. Francomano: Grants/research support; The Ehlers-Danlos Society. R. Bascom: None. L. Bloom: Corporate appointments; The Ehlers-Danlos Society.